(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
The preservation of ‘electoral democracy’ in the digital era Across both sides of the Atlantic, recent electoral cycles have revealed significant distortions in electoral processes. The use of media manipulation techniques, the widespread dissemination of misleading information, and the opaque management of campaign financing have led to systematic violations of electoral legislation during the conduct of electoral campaigns. These phenomena – due to their disruptive potential – have proven capable of undermining the very foundations of democratic systems, potentially pushing them toward illiberal forms of governance. Starting from a critical analysis of the main developments surrounding the 2024 presidential elections in the United States and Romania, this paper explores the preservation of electoral safeguards and, more broadly, the resilience of liberal democracy in the digital age.